Social Education Campaign Through Studi Independen of a Better World Academy in Central Java - Khomsani, Ima; Tijan, Tijan; Suhardiyanto, Andi; Saputro, Iwan Hardi (Unnes Political Science Journal, 2023)
This research was motivated by the declining quality of Indonesian education and educational challenges due to the Covid-19 pandemic. This problem gave birth to various educational innovations, one of which is the A Better World Academy Study to improve the quality of education and the implementation of social campaigns in Jawa Tengah. The social campaign in Jawa Tengah aims to help provide facilities and infrastructure for Sanggar Genius Yatim Mandiri and provide awareness of the importance of education. This research uses qualitative methods in activities. Research data collection is obtained through primary and secondary data sources. Data validity techniques in this study use source triangulation and data analysis techniques and techniques. The results of this study show: 1) The platforms used in activities are Thinkific, Slack, Zoom Meeting, Google Drive, Email, and Whatsapp which use concepts and provisions as needed. 2) The learning process of activities has a clear flow, types and indicators ranging from Welcoming Students to Graduation Day. 3) The implementation of this educational social campaign seeks to increase awareness of education, especially the education of orphans and duafa and improve facilities and infrastructure 7 Orphan Genius Workshops in Jawa Tengah.